Variations for piano in F major, op. 34 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Odescalchi, Barbara, Fürstin von, 1780-1813 (dedicatee):::Contributor:::::::::::: (Leipzig; Germany; Breitkopf & Härtel)
First edition of the Variations for piano in F major, op. 34, published April 1803.